PEMETEAAN KOMPETISI PERGURUAN TINGI DENGAN BRAND MEASUREMENT - Hendy Tannady (Universitas Bunda Mulia, 2017)
The right strategy execution by business and commercial organizations expected to improve performance, however the current corporate strategy is viewed no longer enough, and should start paying attention to imaging as a means to seize the market, the brand can also be seen as something that can strengthen or weaken the positioning in the eyes of the market. Mapping of corporate brand Is reviewed from the point of evalution and relevance should be right on target and should be used as supportive data for making short and long term strategy of the organizations.This research discussed about how mapping the universities brand, mapping activities was divide in to three measurement, which is Brand Awareness, Brand Preference and Brand Perception. This research also segementing respondents in two segments, senior high school students and parents, this research located in West Jakarta, research target is mapping universities brand in national context, thus universities in answer separate in national universities.Result from this research showing that University of Indonesia is Top of Mind in senior high school students Brand Awareness with 19,17% and Tarumanagara University is Top of Mind in parents brand awareness with 28,33%. Whereas brand preference result in University of Indonesia is the most preference in students and parents perpectives with 24,17% and 27,5%.Keywords : Brand, Universities, Brand Awareness, brand preference, brand perception